Kebijakan Eknomi Amerika Serikat terhadap Taiwan Tahun 1951-1965 - Apriliyani, Ni Putu Wulan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 03 (2015), 2015)
ABSTRAK This research describesthe national interest of the United State  in providing foreign aid to Taiwan. Foreign aid from the United Statebegan in 1951 until 1965. After Taiwan decided for ourselves, the state of the economy in Taiwan is still not stable. Therefore, the United State give foreign aid to help the growth of the economy of Taiwan. This would help the United state maintain stability in the Taiwan economy thus simplifying the process of democratization. Keywords : foreign aid, national interest, democratization